Spontaneous Uterine Perforation due to Pyometra Presenting as Acute Abdomen - Loabat Geranpayeh; Mohsen Fadaei-Araghi; Behnam Shakiba (Hindawi Limited, 2006)
Spontaneous perforation of the uterus is rare, its incidence being about 0.01%-0.05%. We report a rare case of diffuse peritonitis caused by spontaneously perforated pyometra. A 63-year-old woman with severe abdominal pain was admitted to our hospital. Laparotomy was performed because of the suspicion of gastrointestinal perforation with generalized peritonitis. At laparotomy, about 900 mL of pus was found in the peritoneal cavity. There were no abnormal findings in the alimentary tract, liver, or gallbladder. A total abdominal hysterectomy with bilateral salpingo-oophorectomy was performed. Pathological investigation of the surgical specimen revealed endometritis and myometritis of the uterus; but there was no evidence of malignancy, and the cervical canal was patent. Although spontaneously perforated pyometra is rare, a perforated pyometra should therefore also be considered when elderly women present with acute abdominal pain.